An Empirical Investigation of the Relationship between Institutional Aspect and Supply Chain Strategy in Relation to Investment Policy in Indonesia - M Widaningsih; Budiman Rusli; Margo Punomo; Candradewini . (International Journal of Supply Chain Management, 2018)
The asset size of institutional investment in Indonesia is only about 6% of its GDP which is an obvious indication of a very weak potential of investors to contribute to countrys development plans or its infrastructure development. Hence, most asset managers and institutional investors fail to get any opportunity to work with Big Data analytics or financial supply chain management (SCM) practices. Due to a relatively restricted workflow and a very small volume of data to dispose, they mostly depend upon manual spreadsheets and primitive financial accounting methods. As a result, the data available for investors to make investment decisions are very limited in scope, lacking metrics for analysis. This study investigated the interrelationship of such institutional investors with supply chain practices. The results revealed that manually kept data of Indonesia investors are not properly organized nor are retrievable from their archives. The data of this study was collected through interviews of portfolio and asset managers, brokers and commissioned agents in banks, insurance and stock institutions of Indonesia. The theoretical framework of this study enabled to understand the scope of institutional investments in different scenarios. The findings reveal the evolution of such practices like sustainable SCM and green SCM that have strengthened the institutional investment patterns in Indonesia.